Reference Services in the library: literature review - Yasmin, Aulia Naurah; Fadilah, Isra Nur; Mutia, Fitri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
This research aims to investigate the impact of reference services on the library and the professionalism of librarians on library users. This research explains the importance of libraries, especially those in higher education institutions, in assisting people in obtaining information. To assess the level of satisfaction among library users, this research employs a literature review method. Before determining the results, 150 articles were initially reviewed, then screening was conducted, resulting in 70 articles. These were further filtered down to 20 articles for the final review. The result of this research is libraries, reference services, librarians, and user satisfaction are interconnected elements that support effective information dissemination and academic activities in higher education.